Pengalaman Komunikasi Anggota Pemuda Pancasila dalam Organisasi Masyarakat di Kecamatan Tarumajaya - Nisa, Choirun; Utamidewi, Wahyu; Nurkinan, Nurkinan (Peneliti.net, 2024)
This study explores communication experiences, motivations, and meaning within the Pemuda Pancasila community organization in Tarumajaya district, Bekasi. Using qualitative methods and Alfred Schutz's phenomenological framework, it examines internal and external communication dynamics, reasons for joining, and the significance of membership. Data collection involves interviews, observations, and document analysis, with thematic analysis focusing on communication, motivation, and meaning. The findings reveal complex communication experiences and various motivations for joining, from societal contributions to upholding Pancasila's values. The study also explores the meaning members attribute to their roles and how communication experiences influence this. This research offers valuable insights into Pemuda Pancasila members in community organizations, aiding our understanding of their role in the broader social context and informing policies supporting youth participation in community development.